Spatiotemporal variations in surface marine carbonate system properties across the western Mediterranean Sea using volunteer observing ship data - D. Curbelo-Hernández; D. González-Santana; A. G. González; J. M. Santana-Casiano; M. González-Dávila (Biogeosciences)
Surface physical and marine carbonate system (MCS) properties were assessed along the western boundary of the Mediterranean Sea. An unprecedented high-resolution observation-based dataset spanning 5 years (2019–2024) was built through automatic underway monitoring by a volunteer observing ship (VOS). The MCS dynamics were strongly modulated by physical–biological coupling dependent on the upper-layer circulation and mesoscale features. The variations in CO2 fugacity (fCO2,sw) were mainly driven by sea surface temperature (SST) changes. On a seasonal scale, SST explained 51 %–71 % of the increase in fCO2,sw from February to September, while total alkalinity (AT) and sea surface salinity (SSS) explained < 20 %. The processes controlling total inorganic carbon (CT) partially offset this increment and explain ∼ 23 %–37 % of the fCO2,sw seasonal change. On an interannual scale, the SST trends (0.26–0.43 °C yr−1) have accelerated by 78 %–88 % in comparison with previous decades. The ongoing surface warming contributed ∼ 76 %–92 % to increasing fCO2,sw (4.18 to 5.53 µatm yr−1) and, consequently, decreasing pH (−0.005 to −0.007 units per year) in the surface waters. The seasonal amplitude of SST, which is becoming larger due to progressively warmer summers, was the primary driver of the observed slope of interannual trends. The evaluation of the air–sea CO2 exchange shows the area across the Alboran Sea (14 000 km2) and the eastern Iberian margin (40 000 km2) acting as an atmospheric CO2 sink of −1.57 ± 0.49 mol m−2 yr−1 (−0.97 ± 0.30 Tg CO2 yr−1) and −0.70 ± 0.54 mol m−2 yr−1 (−1.22 ± 0.95 Tg CO2 yr−1), respectively. Considering the spatial variability of CO2 fluxes across the study area, a reduction of approximately 40 %–80 % in the net annual CO2 sink has been estimated since 2019, which is attributed to the persistent strengthening of the source status during summer and the weakening of the sink status during spring and autumn.